Design-thinking skill enhancement in virtual reality: A literature study - Lyu, Qiner; Watanabe, Kentaro; Umemura, Hiroyuki; Murai, Akihiko (Frontiers in Virtual Reality, 2023)
As a methodology, design thinking involves practicing “a way of thinking” that nondesigners can use as a source of inspiration instead being limited to a group of professional designers; this methodology has gained research attention because of the growing demands for social innovation and sustainability. The general public is expected to gain design-thinking skills through training or by applying design-thinking tools; virtual reality (VR) is considered a potential tool to help accelerate augmenting design-thinking skills because it allows users to have embodied and immersive experiences. This study reviews existing literature on how VR has been used to enhance design-thinking skills. The general features of the publications such as the year of publication, design-thinking stages, VR types, targeted participants, and publication fields are analyzed for determining the latest trends and scenarios under this research topic. Further, a thematic analysis that follows creative enhancement structures is conducted to understand the role of VR in enhancing design-thinking skills, and future research directions are discussed based on the results. The review concludes that VR has the potential to enhance creativity in many aspects, and the need of gaining deeper understanding about (1) art, humanities, and societal perspectives; (2) cognition processes in VR; (3) emphasizing and defining stages in the design-thinking process; (4) technological improvements combined with the Metaverse; and (5) hybrid of the virtual and real worlds.